2008
DOI: 10.1097/shk.0b013e31812385da
|View full text |Cite
|
Sign up to set email alerts
|

STIMULATION OF ADENOSINE A2A RECEPTOR INHIBITS LPS-INDUCED EXPRESSION OF INTERCELLULAR ADHESION MOLECULE 1 AND PRODUCTION OF TNF-α IN HUMAN PERIPHERAL BLOOD MONONUCLEAR CELLS

Abstract: LPS stimulates CD14/Toll-like receptor (TLR) 4, leading to induce TNF-alpha production. Cell-to-cell interaction through the engagement between intercellular adhesion molecule (ICAM) 1 on monocytes and its ligand on T cells has been suggested to play a role in the TNF-alpha production by LPS-treated human peripheral blood mononuclear cells (PBMCs). Adenosine is reported to inhibit LPS-induced TNF-alpha production. However, little is known about the mechanism of the inhibitory effects induced by adenosine on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Nicotine dose dependently reduced TNF production in 4 out of 11 human whole blood samples, whereas in one sample TNF release was enhanced. Other studies report that in other cell types, such as peripheral blood-derived human macrophages [1] and mononuclear cells [36], nicotinic receptor activation reduced TNF production in all samples. On the other hand, Kox et al [37] reported that nicotine attenuated TNF release equally on PBMCs, monocytes and human whole blood samples, but only at a high dosage of 1 m M .…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine dose dependently reduced TNF production in 4 out of 11 human whole blood samples, whereas in one sample TNF release was enhanced. Other studies report that in other cell types, such as peripheral blood-derived human macrophages [1] and mononuclear cells [36], nicotinic receptor activation reduced TNF production in all samples. On the other hand, Kox et al [37] reported that nicotine attenuated TNF release equally on PBMCs, monocytes and human whole blood samples, but only at a high dosage of 1 m M .…”
Section: Discussionmentioning
confidence: 99%
“…ADORA2A is an important regulator of inflammation in other models of injury, yet the actions of ADORA2A in macrophages remain largely unknown (25,29,(45)(46)(47)(48). Because CGS-21680 does express weak affinity for another adenosine receptor, ADORA2B (1/100 potency compared with ADORA2A), we used NECA as a nonselective AR agonist to assess the potential additional contribution of ADORA2B to the observed response in our model (11).…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine inhibits LPS-induced production of TNF by murine peritoneal macrophages but increases that of IL-6 [21,27]. A2AR activation, with the selective adenosine congener 2- p -(2-Carboxyethyl)phenethylamino-5′- N -ethyl-carboxamidoadenosine (CGS-21680), inhibits LPS-induced TNF production in human peripheral blood mononuclear cells (PBMCs) [28], monocytes [29], human lung macrophages [30] and murine macrophages [31]. The AR agonist 5′- N -ethylcarboxamidoadenosine (NECA) activated A2AR and increased cAMP in human monocytes thereby inhibiting LPS-induced IL-12p70 while enhancing IL-10 production in human whole blood [23].…”
Section: Adenosine In Innate Immunitymentioning
confidence: 99%